Strengths and limitations of a tool for monitoring and evaluating First Peoples' health promotion from an ecological perspective. (December 2015) - Rowley, Kevin; Doyle, Joyce; Johnston, Leah; Reilly, Rachel; McCarthy, Leisa; Marika, Mayatili; Riley, Therese; Atkinson, Petah; Firebrace, Bradley; Calleja, Julie; Cargo, Margaret
Abstract Background An ecological approach to health and health promotion targets individuals and the environmental determinants of their health as a means of more effectively influencing health outcomes. The approach has potential value as a means to more accurately capture the holistic nature of Australian First Peoples' health programs and the way in which they seek to influence environmental, including social, determinants of health. Methods We report several case studies of applying an ecological approach to health program evaluation using a tool developed for application to mainstream public health programs in North America – Richard's ecological coding procedure. Results We find the ecological approach in general, and the Richard procedure specifically, to have potential for broader use as an approach to reporting and evaluation of health promotion programs. However, our experience applying this tool in academic and community-based program evaluation contexts, conducted in collaboration with First Peoples of Australia, suggests that it would benefit from cultural adaptations that would bring the ecological coding procedure in greater alignment with the worldviews of First Peoples and better identify the aims and strategies of local health promotion programs. Conclusions Establishing the cultural validity of the ecological coding procedure is necessary to adequately capture the underlying program activities of community-based health promotion programs designed to benefit First Peoples, and its collaborative implementation with First Peoples supports a human rights approach to health program evaluation.